Proposed amendment of the International Code of Zoological Nomenclature to expand and refine methods of publication - On Zoological Nomenclature, International Commission (Zootaxa, 2008)
For 250 years, taxonomists have relied on having access to physical copies of published works in order to verify information about taxa. The difficulty of tracking down publications can be a substantial impediment to taxonomic work, which has led some researchers to advocate modifying the codes of nomenclature, for plants and bacteria as well as for animals, to allow electronic publication of scientific names (Knapp et al. 2007, Wheeler & Krell 2007).